Different functionalized chord and twist distributions in aerodynamic design of HAWTs. Issue 4 (18th March 2019) - Tahani, Mojtaba; Kavari, Ghazale; Mirhosseini, Mojtaba; Ghiyasi, Samira
Abstract : In this study, blade element momentum (BEM) theory has been used to calculate power output and performance of 100 kW and 1 MW horizontal axis wind turbine. Riso‐A1‐21 airfoils are considered as utilized section along the blade span. Generally, Riso family of airfoils is appropriate for wind turbine application. In order to improve the accuracy of turbine performance prediction, lots of corrections have been applied on the BEM method. The aim of this research study is proposing a new procedure to introduce the chord and twist distributions by fitting different types of functions on them. Accordingly, 48 functions are selected as possible distributions for chord and twist angle profiles. These functions are selected in such a way that their behavior is close to the trend of their classical distributions. The utilized design method in this study is optimum in terms of performance and also making distribution of chord and twist functional which is more appropriate for manufacturing process. Finally, the effect of using best functions on blade aerodynamic coefficients has been studied. Results show that despite the changing chord and twist distributions from their classical trends, the aerodynamic coefficients are approximately similar to those in the classical design except in some region of blade. © 2019 American Institute of Chemical Engineers Environ Prog, 38:e13108, 2019